On the relative motions of long-lived Pacific mantle plumes - Kevin Konrad (Nature Portfolio, 2018)
Using mantle plumes to reconstruct past plate motion is complicated, because plumes may not be fixed. Here, the authors demonstrate using 40Ar/39Ar ages that the Rurutu plume is relatively stable compared to the rapidly moving Hawaiian plume, yet it has a similar deep mantle origin.